The Relationship Between Knowledge And Maternal Interest In Using Implant Contraceptives - Betristasia Puspitasari; Rofik Darmayanti (Jurnal EduHealth, 2024)
Implants are an effective hormonal contraceptive method, contain the hormone progestin, are not permanent and can prevent pregnancy between 3 and 5 years. There are indeed several things that make implants unpopular because many people lack the latest information about proper use. The purpose of this study is to determine the relationship between knowledge and maternal interest in using implant contraception. The research design uses correlation with a cross sectional approach. The population in the study of all mothers in RW 02 Ds Cengkok, Nganjuk Regency. The sampling technique using accidental sampling was obtained with a sample of 33 respondents. In this study, two variables were used, namely the independent variable was the mother's knowledge of implant contraception and the dependent variable was the mother's interest in using implan contraception. The research instruments used questionnaires, data processing with editing, coding, scoring, tabulating and data analysis using Spearman Rank. The results of the study were obtained that 18 respondents (54.6%) had sufficient knowledge about implant contraception and 27 respondents (81.8%) had moderate interest in using implant contraception. From the results of the statistical test, it was found that there was a relationship between the knowledge of mothers about implant contraception and interest in using implant contraception based on the results of  Z calculated 3 while Z table was 1.96 where Z counted > Z table, then H1 was accepted. Based on the results of the study, it can be concluded that there is a relationship between knowledge and maternal interest in using implant contraceptives. To increase maternal knowledge about implant contraception, counseling is needed, especially for mothers with low education.